A comparative evaluation of community structure in full-scale digesters indicates that two-phase digesters exhibit greater microbial diversity than single-phase digesters. Issue 2 (16th January 2017) - Smith, A. L.; Shimada, T.; Raskin, L.
Abstract : Sequencing of full-scale, two-phase anaerobic digesters suggested that increased microbial community diversity improves process performance. Abstract : Two-phase (acid-gas) anaerobic digestion can improve process performance relative to conventional, mesophilic, single-phase anaerobic digestion. However, few studies have considered the impact of phase separation on microbial community structure. We compared six full-scale, two-phase digestion (TPD) facilities and four conventional digestion (CD) facilities at municipal wastewater treatment plants by collecting performance data and evaluating microbial community structure via Illumina 16S rRNA gene sequencing. Sequence data indicated that nearly complete phase separation was achieved in all TPDs with few syntrophic bacteria or methanogens detected in acid phase digesters (APDs). Thermophilic methane phase digesters (MPDs) exhibited poor performance relative to mesophilic MPDs consistent with substantially lower relative abundances of syntrophic bacteria and methanogens in thermophilic MPDs. Although known syntrophic acetate oxidizers were only detected at very low levels in MPDs (0.11 ± 0.20%), the low abundance of aceticlastic methanogens observed suggests that syntrophic acetate oxidation plays a prominent role by yet to be described populations in TPD. TPDs exhibited greater microbial diversity than CDs, likely due to APDs supporting more diverse populations of hydrolytic and fermentative bacteria.